2019
DOI: 10.1186/s12870-019-1927-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of soil aeration on root morphology and photosynthetic characteristics of potted tomato plants (Solanum lycopersicum) at different NaCl salinity levels

Abstract: Background Salt stress is one of the environmental factors that greatly limits crop production worldwide because high salt concentrations in the soil affect morphological responses and physiological and metabolic processes, including root morphology and photosynthetic characteristics. Soil aeration has been reported to accelerate the growth of plants and increase crop yield. The objective of this study was to examine the effects of 3 NaCl salinity levels (28, 74 and 120 mM) and 3 aeration volume l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(28 citation statements)
references
References 56 publications
0
28
0
Order By: Relevance
“…As a consequence, root meristems in salt-stressed roots are generally reduced in size and therefore produce fewer cells (Azaizeh & Steudle, 1991;Kurth, Cramer, Läuchli, & Epstein, 1986;Zidan, Azaizeh, & Neumann, 1990). In summary, the combination of salt effects on both cell division and cell elongation bean (Liu et al, 2017), rice (Gao et al, 2011), tomato (Hu et al, 2012;Li et al, 2019) and wheat (Shafi et al, 2010). Our study found that root development traits including RLD and RSAD decreased significantly with increasing NaCl concentrations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a consequence, root meristems in salt-stressed roots are generally reduced in size and therefore produce fewer cells (Azaizeh & Steudle, 1991;Kurth, Cramer, Läuchli, & Epstein, 1986;Zidan, Azaizeh, & Neumann, 1990). In summary, the combination of salt effects on both cell division and cell elongation bean (Liu et al, 2017), rice (Gao et al, 2011), tomato (Hu et al, 2012;Li et al, 2019) and wheat (Shafi et al, 2010). Our study found that root development traits including RLD and RSAD decreased significantly with increasing NaCl concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research suggested that root traits including root length, surface area, and volume of spindle, soybean, rice, tomato and wheat decreased significantly with increasing NaCl concentrations; and varied among accessions in each species (Gao et al, 2011;Gómez-Bellot et al, 2013;Hu et al, 2012;Li et al, 2019;Liu et al, 2017;Shafi et al, 2010). In quinoa, many studies focused on varietal differences in morphological traits under saline stresses (Arshadullah et al, 2016;Eisa et al, 2012;Peterson & Murphy, 2015;Prado, Boero, Gallardo, & González, 2000;Ruiz-Carrasco et al, 2011); however, root development responses still remain largely unknown.…”
Section: Introductionmentioning
confidence: 97%
“…Root architecture can be changed in response to NaCl toxicity, as mentioned by Van Hoorn et al (2001), Flores et al (2002), Mahajan and Tuteja (2005), and Shafi et al (2010). Adverse effects of NaCl limiting root growth in tomato plants are reported by Li et al (2019b). Under salt stress, root growth is reduced from many possible reasons.…”
Section: Discussionmentioning
confidence: 99%
“…Yin et al (2019) described its protective ability against abiotic stress in plants. Li et al (2019b) suggested the involvement of melatonin in enhancing tolerance under both biotic and abiotic stresses in tomato plants, by regulation of several biological processes. Galano et al (2011), Zhang et al (2015), and Zhang et al (2019) also witnessed the efficiency of exogenous melatonin in different crops for the amelioration of adverse effects of different stresses.…”
Section: Introductionmentioning
confidence: 99%
“…Decrease in intracellular CO 2 concentration and photosynthesis during salinity stress due to stomatal closure leads to lesser availability of CO 2 to the RuBisCO enzyme binding, thereby enhancing the rate of photorespiration ( Igamberdiev, 2015 ). Salinity stress-induced accumulation of excess salts is known to affect the function of photosystems by modulating the photosynthetic proteins in chloroplasts causing irreversible damage to the photosynthetic apparatus at all developmental stages in glycophytic plants ( Sun et al, 2016 ; Li et al, 2019 ; Rodríguez-Ortega et al, 2019 ; Zhang et al, 2020 ). Adaptation of plants to salinity stress involves modification of complex physiological traits, metabolic pathways, and gene networks ( Nounjan et al, 2012 ; Gupta and Huang, 2014 ; Ghorbani et al, 2018 ; Kumar et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%